2022
DOI: 10.1521/jscp.2022.41.4.365
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Social Media Exposure on Body Dissatisfaction and Eating Behavior of Male and Female Students

Abstract: Introduction: Experimental research has examined the effect of social media on body dissatisfaction, but little attention has been given to the impact on eating behavior. Across two studies, we tested the causal relationship between acute social media use, body dissatisfaction and eating behavior. Methods: In Study 1, 80 female participants (age: M = 20.75 years; BMI: M = 21.3) viewed their own Facebook account or a news website before completing a portion size selection task. In Study 2 (pre-registered), 148 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In this sense, the results of our work have confirmed that there are significant correlations between the level of exposure of adolescents to food or body care advertising on social networks and the level of satisfaction with their physical appearance (RQ 1). Specifically, the data show that exposure to social networks increases the dissatisfaction that adolescents have with their own bodies, which, as previous studies have shown, can lead to the development of mental health problems such as depressive disorders (Murray et al, 2023), self-esteem problems due to feeling that they do not fit in with the canons of beauty established by society (De-Jans et al, 2021) and agreed upon by social networks, and eating disorders (Cordero et al, 2022;Pink et al, 2022;Sanzari et al, 2023).…”
Section: Discussionmentioning
confidence: 63%
“…In this sense, the results of our work have confirmed that there are significant correlations between the level of exposure of adolescents to food or body care advertising on social networks and the level of satisfaction with their physical appearance (RQ 1). Specifically, the data show that exposure to social networks increases the dissatisfaction that adolescents have with their own bodies, which, as previous studies have shown, can lead to the development of mental health problems such as depressive disorders (Murray et al, 2023), self-esteem problems due to feeling that they do not fit in with the canons of beauty established by society (De-Jans et al, 2021) and agreed upon by social networks, and eating disorders (Cordero et al, 2022;Pink et al, 2022;Sanzari et al, 2023).…”
Section: Discussionmentioning
confidence: 63%
“…Strengths of this study include the large sample with a wide BMI and age range, and the inclusion of a mood and neutral control group. However, there is a need now to examine the effects of viewing such images on BI in other understudied groups, in particular to include males in this research, as they have been neglected in the literature despite becoming increasingly vulnerable to the detrimental effects of having a poor BI (Pink et al, 2022; Rodgers & Rousseau, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Body image (BI) is a multifaceted construct that refers to perceptions of and attitudes toward one’s own body (Cash et al, 2002). Poor BI is related to the development of eating disorders (Tylka, 2004), comorbid mental health outcomes (Woodside & Staab, 2006), and has been attributed to sociocultural factors in young females (Thompson et al, 2004), with research indicating social media, in particular thin-ideal body imagery, as a likely influence (e.g., Brown & Tiggemann, 2016; Pink et al, 2022; Saiphoo & Vahedi, 2019).…”
Section: Self-esteemmentioning
confidence: 99%
“…Pink, A.E. et al stated in 2022 that brief exposure, less than 10 times, leads to a negative impact on consumers physically [20,21]. Nevertheless, a recent study illustrated that the optimal level of ad frequency is ten times of exposure, which may guide advertisers to maximize the purchase intention of consumers in a psychological way [13].…”
Section: Consumer Purchase Intentionmentioning
confidence: 99%